Counseling for fetal heart disease: current standards and best practice - Kovacevic, Alexander; Elsässer, Michael; Fluhr, Herbert; Müller, Andreas; Starystach, Sebastian; Bär, Stefan; Gorenflo, Matthias (Translational pediatrics, 2021)
Counseling for fetal heart disease - current standards and best practice
Gesehen am 14.10.2020